Catalytic influence of 16-s-16 gemini surfactants on the rate constant of histidine and ninhydrin. Issue 2 (5th February 2020) - Kumar, Dileep; Rub, Malik Abdul
Abstract : The present paper reports the catalytic influence of 16- s -16 (spacer ( s ) = 4, 5, 6) gemini surfactants on the rate constant of histidine and ninhydrin at 343 K and pH 5.0 using the spectrophotometric technique. The effect of varying amounts of geminis was made on the rate constant of histidine and ninhydrin keeping other constituents constant. Characteristics of the rate constant ( kψ ) versus [gemini] depict the effect of surfactants on the rate constant. A systematic explanation about the effect of surfactants is revealed and discussed in the text. The influence of different parameters that includes [reactants], temperature and pH has also been performed on the study. In order to determine the critical micelle concentration (cmc) of pure surfactants and their solution mixtures, conductivity measurement was employed. By using the Eyring equation, activation parameters at different temperatures have been obtained. The resultant data of kψ versus [gemini] plot were rationalized with the pseudo-phase model of micelles.